Efforts of Islamic Religious Education Teachers in Preventing the Negative Impact of the TikTok Application on Students - Khidir; Madi; Jufri (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
The use of social media, especially TikTok, has become a significant phenomenon among today's teenagers. Although this platform provides a space for creativity and expression, its impact on student behavior and learning is a serious concern in the educational environment. The negative impacts of TikTok application use among teenagers, including students of Junior High School 1 Buton Tengah, can be traced through several main factors such as gadget addiction, unhealthy lifestyle, and negative influence on mindset. This study aims to explore the efforts of Islamic Religious Education (PAI) teachers in preventing the negative impacts of TikTok use at Junior High School 1 Buton Tengah. Descriptive qualitative methods were used to identify strategies implemented by PAI teachers in directing students to use social media wisely. The findings show that the efforts of PAI teachers are very important in providing moral education and integrating religious values ​​in facing the challenges of social media.